2011
DOI: 10.1093/jac/dkr293
|View full text |Cite
|
Sign up to set email alerts
|

Primary antibiotic resistance of Helicobacter pylori strains isolated from Portuguese children: a prospective multicentre study over a 10 year period

Abstract: The primary resistance rate of H. pylori strains isolated from Portuguese children to the commonly used anti-H. pylori antibiotics used is high. Additionally, the increasing trend of ciprofloxacin-resistant and double-resistant strains may compromise H. pylori eradication in a high-prevalence population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 7 publications
7
49
1
Order By: Relevance
“…The prevalence of levofloxacin resistance was not tested in the previous European study because levofloxacin-based treatment only emerged later 16. Several reports have indicated that the prevalence of resistance of H pylori to quinolones has increased rapidly over the last decade17 18 and that it could soon reach the level of clarithromycin resistance 17. On the other hand, metronidazole resistance remains at the same high level (34.9%) as 10 years ago with no major changes in the regional distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of levofloxacin resistance was not tested in the previous European study because levofloxacin-based treatment only emerged later 16. Several reports have indicated that the prevalence of resistance of H pylori to quinolones has increased rapidly over the last decade17 18 and that it could soon reach the level of clarithromycin resistance 17. On the other hand, metronidazole resistance remains at the same high level (34.9%) as 10 years ago with no major changes in the regional distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to clarithromycin has also risen by > 20% in Southern Europe, although in Northern Europe the resistance rate is less than 10% [45] compared to 1.5% in a random adult Swedish population [46] and 7.5% in central Germany [47] . During the last 15 years, a twofold increase in clarithromycin resistance was reported in Italy [48] and in Spain, where the mean clarithromycin resistance rate was 18.3% in 1709 patients [49] , and 34.7% in Portuguese children [50] . In contrast to the general trend, the rate of H. pylori strains resistant to clarithromycin decreased from 34% to 22% during 6 years in Southern Poland [51] .…”
Section: Current Antibiotic Resistance In Worldwidementioning
confidence: 99%
“…The bacterium is colonized in the stomach of more than 50% of the world's population (2). H. pylori associated infections are treated with antibiotics such as metronidazole, clarithromycin, amoxicillin, tetracycline, and levofloxacin in addition to an acid secretion inhibitor drug (3).…”
Section: Introductionmentioning
confidence: 99%